2016
DOI: 10.1681/asn.2015010023
|View full text |Cite
|
Sign up to set email alerts
|

New Solutions to Reduce Discard of Kidneys Donated for Transplantation

Abstract: Kidney transplantation is a cost-saving treatment that extends the lives of patients with ESRD. Unfortunately, the kidney transplant waiting list has ballooned to over 100,000 Americans. Across large areas of the United States, many kidney transplant candidates spend over 5 years waiting and often die before undergoing transplantation. However, more than 2500 kidneys (.17% of the total recovered from deceased donors) were discarded in 2013, despite evidence that many of these kidneys would provide a survival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 37 publications
1
132
2
1
Order By: Relevance
“…However, we have also shown that IRD kidneys within the low-to-middle range of KDPI (30–50) faced greater scrutiny when considered for transplant and were 2.2-times more likely to be discarded than comparable non-IRD kidneys, while IRD kidneys with higher KDPI (70–100) were only 1.13-times more likely to be discarded than comparable non-IRD kidneys. This analysis indicates that despite the high quality of IRD kidneys, they continue to be regarded with disparate scrutiny for transplantation (22), and it further supports the current discourse on improving utilization of these organs (20, 2325). …”
Section: Discussionsupporting
confidence: 62%
“…However, we have also shown that IRD kidneys within the low-to-middle range of KDPI (30–50) faced greater scrutiny when considered for transplant and were 2.2-times more likely to be discarded than comparable non-IRD kidneys, while IRD kidneys with higher KDPI (70–100) were only 1.13-times more likely to be discarded than comparable non-IRD kidneys. This analysis indicates that despite the high quality of IRD kidneys, they continue to be regarded with disparate scrutiny for transplantation (22), and it further supports the current discourse on improving utilization of these organs (20, 2325). …”
Section: Discussionsupporting
confidence: 62%
“…Accepting a PHS‐IR organ offers survival benefit to recipients compared to those who declined it and are waiting for a PHS‐IR donor offer and staying on dialysis . There exist a notion that a disproportionate number of discarded kidneys originate from PHS‐IR donors . In our study cohort (the kidneys recovered for transplantation), the PHS‐IR kidneys accounted for 23.8% of total organ pool and 21.6% discarded kidneys, and, contrary to common perception, the PHS‐IR kidneys experienced lower discard rates across all HCV groups compared to the PHS‐IR kidneys under same HCV categories.…”
Section: Discussioncontrasting
confidence: 53%
“…While organ discard (3, 4) and sequence of liver acceptance (17) have been previously evaluated, this study reveals important information about how specific donor and DSA factors contribute to position of kidney allograft acceptance in the match-run among organs that are ultimately transplanted. Our results reveal that PHS increased-risk status kidneys are highly disposed to delayed acceptance or discard.…”
Section: Discussionmentioning
confidence: 99%
“…Greater efforts are needed to increase physician and transplant candidate awareness of the high potential utility of these organs, and relatively low infectious risk associated with their use (2123). Changing the allocation process to offer these organs earlier or preferentially to centers with demonstrated willingness to accept them may also reduce turndown, CIT, and potentially discard (3). This issue is especially timely given the opioid crisis, which has led to a high prevalence of potential donors categorized as PHS increased-risk in certain regions (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation